Learning Mathematics Through Videos Lines and Angles: How to Analyze Students' Understanding of Mathematical Concepts? - Rohmah, Riska Nur; Setyaningrum, Wahyu (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The use of technology through learning videos has a high-quality impact on students' understanding of mathematical concepts. However, the facts show that the use of learning videos has not been fully utilized, especially in the lines and angles material. The purpose of this research is to determine and describe students' understanding on lines and angles concepts through the use of instructional videos. This study is a qualitative descriptive approach which employed interviews of students' conceptual understanding after their taking a test. This research involved two seventh-grade students of a junior high schools in Tulungagung, namely AL and YL. Both research subjects have studied the material of lines and angles in mathematics learning through the use of mathematics learning videos. The two students in this study were also students with high learning achievement categories. The results obtained from this study stated that the average ability of students to understand mathematical concepts was 80 out of a maximum score of 100 which can be categorized a good level of conceptual understanding. This implies that mathematics learning videos can be used as an alternative for teachers and other researchers in conveying material, and training students' abilities in understanding mathematical concepts, especially lines and angles material. As for further research, students' ability to understand mathematical concepts can be supported by using worksheets, media, or other learning approaches on lines and angles material.